Risk riding behaviours of young motorcyclists among students in Universiti Putra Malaysia, Serdang, Selangor - Ahmad, Noor Sakinah; Karuppiah, Karmegam; How, Vivien; Md Isa, Mohd Hafzi; K.C. Mani, Kulanthayan (Universiti Putra Malaysia Press, 2022)
Introduction: Road accidents involving young motorcyclists are one of the most concerning safety issues in Malaysia. Motorcyclists in Malaysia have a higher vulnerability towards risk and a higher possibility of involving in commuting accidents. Most of these risks are related to the motorcyclist’s riding behaviour. Most of the youngster use motorcycles as their daily mode of transportation. However, less study has been conducted to analyze these young motorcyclists (university students) riding behaviour. Therefore, this study aims to determine the riding behaviours of this young motorcyclist. Methods: This study used a cross-sectional study design and a simple random sampling method. It was conducted among 184 respondents (92 males and 92 females) in Universiti Putra Malaysia, Serdang, Selangor. The respondents were given the self-administered Motorcycle Rider Behaviour Questionnaire (MRBQ) containing 59 items adapted from previous studies. Results: The males had higher crash involvement in both road accidents and near-miss accidents compared to female respondents. The traffic error (p = 0.009), speeding p = 0.001), safety violations (p = 0.001), and safety equipment (p = 0.003) were significantly difference between both male and female students. Safety violation and precautions were the significant road accident predictors among UPM young motorcyclists. Conclusion: Thus, several prevention programs should be conducted to educate them on motorcycle safety riding. It is intended as an early prevention for this young motorcyclist, which in the long term will have a positive impact on reducing commuting accidents in the future.